2021
DOI: 10.1007/s11998-021-00535-4
|View full text |Cite
|
Sign up to set email alerts
|

Shear orientation of nematic phases of clay nanosheets: processing of barrier coatings

Abstract: When suspensions are exposed to shear forces, the particles may form ordered structures depending on their shapes, concentrations, and the material. For some processes, e.g., for wet-film coating, it is important to know how fast these structures form in shear fields and for how long the structures persist when the shear is relaxed. To obtain information on the particle structure formation and the decay time, the effective viscosity of nematic suspensions of Na-hectorite nanosheets was investigated by rheology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Slot die coating is a universally applicable coating tool that can be easily adapted to an industrial scale with high throughput. Recently, we showed that it is ideally suitable for processing nematic phases consisting of high aspect ratio nanosheets . It gives access to perfectly textured 1D “single domain crystalline” wet films, where the nanosheets are aligned in parallel with the PET substrate due to the high shear fields beneath the lips of a slot die.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Slot die coating is a universally applicable coating tool that can be easily adapted to an industrial scale with high throughput. Recently, we showed that it is ideally suitable for processing nematic phases consisting of high aspect ratio nanosheets . It gives access to perfectly textured 1D “single domain crystalline” wet films, where the nanosheets are aligned in parallel with the PET substrate due to the high shear fields beneath the lips of a slot die.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we showed that it is ideally suitable for processing nematic phases consisting of high aspect ratio nanosheets. 46 It gives access to perfectly textured 1D "single domain crystalline" wet films, where the nanosheets are aligned in parallel with the PET substrate due to the high shear fields beneath the lips of a slot die. The shear-oriented nanosheets have sufficient inertness to maintain their orientation upon solvent removal and drying, yielding outstanding barrier coatings with clay nanosheets oriented parallel to the flat substrate.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…First, nematic phases of fully delaminated layered silicates of this high-aspect ratio are already honey-viscous at 3 vol %. Although the suspensions show shear thinning, 43 this represents an upper limit for the concentration regardless of the coating technique, and in any case, >90% water has to be removed. Second, with the low amount of nematic aqueous suspension added for each spraying cycle, drying times are short, which kinetically hinders phase separation within the dry nanocomposite barrier film upon water removal, as recently reported for PVOH and Hec nanocomposite barrier films.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This allows us to study the influence of the perfect hybrid Bragg stack structure of the nanocomposite barrier film as we believe that the alternating layers of PEG and Hec nanosheets that mechanically decouple adjacent silicate nanosheets are crucial to the stretchability, as discussed in detail later. However, barrier films made of nematic Hec suspension fabricated via slot die coating, and industrially benign processing that can easily be transformed to large scale, have already been proven to exhibit extraordinary barrier properties comparable to nanocomposites obtained by spray coating. ,, …”
Section: Resultsmentioning
confidence: 99%
“…Resulting nanocomposite layers lack folding or crumbling defects of the nanosheets and instead present a perfect texture with all nanosheets aligned isotopically in the plane of the film. [ 33 ] The thickness of the wet layer can be tuned by machine parameters, and the dry layer thickness can be tuned by adjustment of suspension solid content (PLA + clay). Each wet layer is partially dried before the subsequent layer is coated on top, with partial solvation of the previous layer by the wet layer ensuring adhesion.…”
Section: Resultsmentioning
confidence: 99%